Pengaruh Pembelajaran Mahfuzhat Terhadap Akhlak Santri Pondok Pesantren Modern Darusslam Kepahiang Bengkulu - Nurhaliza (JPT : Jurnal Pendidikan Tematik, 2021)
The purpose of this study was to determine how the process of implementing Mahfuzhat Learning and the Effect of Mahfuzhat Learning on the Morals of Santri Islamic Boarding School Darussalam Kepahiang Bengkulu. Research Methods, in this study using quantitative research with an associative approach and using statistical calculations used to test the X variable against the Y variable, this research was carried out at the Modern Darussalam Islamic Boarding School Kepahiang Bengkulu and was carried out on March 7 to April 21, 2022. Population in this study all Santri Madrasah Aliyah Private Islamic Boarding School Darussalam Kepahiang. The number of samples is 44 students and the sample collection technique in this study the author uses a stratified random sampling technique. The data collection technique in this research is by using a questionnaire and documentation. The instrument in this study used a Likert scale. Based on data analysis from the results of the research conducted, it can be concluded that Mahfuzhat Learning has a positive effect on the Morals of the Modern Islamic Boarding School Darussalam Kepahiang Bengkulu with a simple linear regression equation, namely Y = 30.650 + 0.473X, which means that for every increase in one variable X, the value of variable Y will increase. of 0.15 actions, which can be concluded that Mahfuzhat Learning affects the Santri's morality 25% seen from the coefficient of determination while 75% is influenced by other variables.